2014
DOI: 10.1165/rcmb.2012-0530oc
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cilia-Driven Transport in the Airways in the Absence of Mucus

Abstract: Airway mucus is thought to be required for the clearance of inhaled particles by mucociliary transport, but this view has recently been challenged. To test if mucus is necessary for cilia-driven particle transport, we removed mucus from murine and human ex vivo airway preparations by thorough rinsing with buffer with or without additional dithiothreitol washing. The transport of particles with diameters of 4.5 μm, 200 nm, and 40 nm and of bacteria was analyzed by video microscopy. Complete removal of mucus was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Con sistent with our previous results, IL-13 markedly reduced the velocity of microspheres prior to removal of the gel. It was recently reported that removal of the mucus gel from healthy airways did not abolish particle transport but instead modestly increased transport velocity (21). We obtained similar results after removal of gels from unstim ulated cultures.…”
Section: Muc5ac-containing Domains Of Mucus Are Tethered To the Airwasupporting
confidence: 86%
“…Con sistent with our previous results, IL-13 markedly reduced the velocity of microspheres prior to removal of the gel. It was recently reported that removal of the mucus gel from healthy airways did not abolish particle transport but instead modestly increased transport velocity (21). We obtained similar results after removal of gels from unstim ulated cultures.…”
Section: Muc5ac-containing Domains Of Mucus Are Tethered To the Airwasupporting
confidence: 86%
“…These aggregates bound to ciliated cells and increased ciliary beat frequency. Furthermore, microscopically visible nanoparticle agglomerates have been shown to increase ciliary beat frequency in the murine trachea [72]. A similar effect has been observed in the bovine trachea where polystyrene particles >200 nm in diameter that attach to cilia increase ciliary beat frequency due to mechanical stimulation of axonema possibly involving second messengers such as cAMP or cGMP [73], both of which are known to increase ciliary beat frequency [74].…”
Section: Discussionmentioning
confidence: 91%
“…The strength of short-term organ culture models is that they can be adapted to screen for specific organ functions that are not routinely examined in standardized in vivo experiments. This was demonstrated by using our ex vivo trachea model that allowed examining the complex interplay between mucus production, ciliary beating and cell death [72, 89]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been used to study the effects of mucus removal on flow [108,109], the effects of physiological stressors [135], and development of directional flow in the trachea [136]. It also became the primary method of estimating mucus velocity in bronchoepithelial cell culture [23,137139].…”
Section: Microscale Imaging Of Cilia-driven Fluid Flowmentioning
confidence: 99%